The study on the best smartphones applications for comic reading and publishing during a pandemic/ Muhammad Zamer Zulkifli ... [et al.] - Zulkifli, Muhammad Zamer; Mohd Shuib, Ahmad Sofiyuddin; Mohd Pahme, Nur Faizah; Abdullah, Anwar Fikri; Rizkavirwan, Darfi (Universiti Teknologi MARA, Perak, 2023)
The adoption and continuous advancement of technology has permeated society, changing the way people interact with technology itself and with the help of technology. Nowadays there are many modern devices are being invented to help with our daily life, including Smartphones, which are widely used around the world. In early 2020, Covid-19 was confirmed, which spread all over the world. The Covid-19 outbreak has made a huge difference in people's lives and economic effects including a lacking source of entertainment like reading a comic book for the people who are locked down during the pandemic. This has led Comic publishers or artists to have a difficult time finding an audience during the pandemic physically. Hence, these Comic publishers and retailers have to adapt to a digital platform 'mobile publishing' for smartphone users through a mobile applications approach since smartphone usage worldwide has increased according to the studies. Therefore, this paper will discuss the best smartphone applications for Comic artists to publish their work as a step to find an audience during the pandemic.